Optical coherence tomography angiography in pseudophakic cystoid macular oedema compared to diabetic macular oedema: qualitative and quantitative evaluation of retinal vasculature. Issue 12 (20th February 2018) - Sacconi, Riccardo; Corbelli, Eleonora; Carnevali, Adriano; Mercuri, Stefano; Rabiolo, Alessandro; Querques, Lea; Marchini, Giorgio; Bandello, Francesco; Querques, Giuseppe
Abstract : Aims: To describe optical coherence tomography angiography (OCT-A) abnormalities of patients with pseudophakic cystoid macular oedema (PCMO) before and after pharmacological resolution, compared with diabetic macular oedema (DMO) and normal eyes. Methods: In this retrospective, observational study, 44 eyes (30 patients) were included: 15 eyes (15 patients) affected by PCMO; 14 healthy fellow eyes used as negative control group; 15 eyes (15 age-matched and sex-matched patients) with DMO used as positive control group. All patients underwent a complete ophthalmological examination at baseline, including OCT-A scans of the macula through AngioPlex CIRRUS-5000 (Carl Zeiss Meditec, Dublin, USA). Patients with PCMO and DMO were re-evaluated after the pharmacological resolution of cystoid macular oedema (CMO). Results: Disruption of parafoveal capillary arcade and cystoid spaces in deep capillary plexus (DCP) were frequent in patients with PCMO and DMO (73% and 100%, 87% and 100%). Capillary abnormalities and non-perfusion greyish areas in DCP were more frequent in DMO (P<0.001 and P=0.014). Patients with PCMO showed a larger foveal avascular zone area in DCP at baseline (P<0.001), which significantly reduced after treatment (P=0.001). Vessel density of full-thickness retina and DCP was reduced in patients with PCMO (P=0.022 and P=0.001), and no changes were observed after treatment. Interestingly, DCP appeared less represented in patients with DMO than PCMO subjects (P=0.001). Conclusions: Patients with PCMO have an impairment of mainly DCP, partially reversible after treatment. Furthermore, we disclosed that different alterations of the retinal vasculature characterise CMO derived from two different diseases, namely PCMO and DMO, and this could be due to their distinct pathophysiology.